On Spaces of Boundary Values for Relations Generated by a Formally Selfadjoint Expression and a Nonnegative Operator Function - Bruk, V.M. (Журнал математической физики, анализа, геометрии, 2006)
The space of boundary values for a maximal relation generated by a formally selfadjoint di erential expression and a nonnegative operator function is constructed.